Advanced Packed-Bed Ca-Cu Looping Process for the CO2 Capture From Steel Mill Off-Gases - Fernández, José Ramón; Spallina, Vincenzo; Abanades, Juan Carlos (Frontiers in Energy Research, 2020)
A novel configuration of the Ca-Cu looping process based on dynamically operated packed-bed reactors is proposed to convert blast furnace gas (BFG) into H2/N2 and highly concentrated CO2, accompanied by a large amount of high-temperature heat. Preliminary energy and mass balances of the process reveal that around 30% of the BFG can be upgraded via calcium assisted WGS if only BFG is used as reducing gas in the reduction/calcination stage. A higher amount of H2/N2 can be produced by using other steel mill of gases (e.g. COG, BOFG) or natural gas in the regeneration of the CO2 sorbent. This decarbonized fuel gas could be used for onsite power generation or to obtain sponge iron by a DRI process, increasing the overall capacity of the steel plant. Energy efficiencies higher than 75% have been calculated, reaching maximum values around 88% in case of using natural as fuel gas for the sorbent regeneration stage. Low values for the specific energy consumption of around 1.5 MJLHV/kgCO2 and CO2 capture efficiencies higher than 95% support the further development of the proposed Ca-Cu looping process.